RESULTS OF THE AUDIT OF CALCULATIONS WITH PERSONNEL ON PAYMENT IN THE ORGANIZATIONS OF RETAIL TRADE - A. Samartseva; Z. Chebotareva (Вестник университета)
The goal and main tasks of audit of calculations with personnel on remuneration of labor are considered. The most common mistakes of accountants in accounting for payroll calculations with employees have been studied. Possible causes of these violations have been identified, as well as the consequences of non-compliance with labor laws for the employer and legal entity. For each violation advice is given on improving the accounting of payroll calculations and minimizing the number of errors.